IMPLEMENTASI PERATURAN PRESIDEN NOMOR 16 TAHUN 2018 TENTANG PENGADAAN BARANG DAN JASA PADA BADAN KEUANGAN DAERAH DI KABUPATEN TABANAN - Kadek Ariyoga; Anak Agung Putu Wiwik Sugiantari (Jurnal Hukum Mahasiswa, 2021)
In carrying out the obligation to provide for the needs of the people as well as the implementation of government activities, the government is required to provide the needs of both goods, services and. infrastructure development. To fulfill goods and services carried out by the government, procurement is classified as a type of contract that is expenditure. One of the government activities included in the expenditure contract is the procurement of goods and services. This research uses a descriptive Empirical Law research method, which aims to accurately describe the characteristics of an individual or group to determine whether or not there is a relationship between a legal phenomenon in society. The results of this study state that the procedures and mechanisms for direct procurement of goods at the Regional Finance Agency in Tabanan Regency run in accordance with Presidential Regulation Number 16 of 2018 concerning the Procurement of Goods and Services. The factors that influence the implementation of direct procurement of goods at the Regional Finance Agency in Tabanan Regency are supporting factors and inhibiting factors.